Heisenberg-Limited Metrology: Utilizing Entangled States for Ultra-Precise Gravitational Wave Detection - Nurul Huda; Ming Pong; Pedro Silva (Yayasan Adra Karima Hubbi, 2026)
Gravitational wave detection has reached unprecedented sensitivity through interferometric technologies, yet it remains fundamentally constrained by quantum noise, particularly the standard quantum limit (SQL). Advances in quantum metrology suggest that entangled states can surpass classical limits and approach the Heisenberg limit, offering a pathway to ultra-precise measurements. This study aims to investigate the potential of entangled quantum states to enhance sensitivity in gravitational wave detectors under realistic conditions. A theoretical–computational approach was employed, combining analytical modeling with large-scale numerical simulations of interferometric systems. Various quantum states, including NOON states, squeezed states, and hybrid entangled–squeezed configurations, were evaluated using quantum Fisher information and phase variance as performance metrics. The results indicate that entangled states achieve Heisenberg-limited scaling in ideal conditions, significantly outperforming classical and squeezed states. Hybrid states demonstrate superior robustness against loss and decoherence, maintaining enhanced sensitivity in non-ideal environments. These findings suggest that the integration of entangled states into interferometric detectors can substantially reduce quantum noise and improve detection capabilities. This study concludes that entanglement-based metrology offers a promising and practical pathway toward next-generation gravitational wave detection with ultra-high precision.